Ibn Khaldun's Material Religious Pragmatic Ideas Are Relevant To The Goals Of Today's Education - Yudiyanto, Mohamad; Martiadi, Rizwan; Mulyani, Ani Sri; Agustini, Riyanti (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
The purpose of this study is to elaborate on the pragmatic religious ideas of Ibn Khaldun, and their relevance to the purpose of education today. The research method used is library research, with observation and documentation data collection techniques. Meanwhile, the research analysis used is qualitative data analysis. The results of the study show, from the social side, that students are able to benefit other humans by not abandoning the obligation to maintain their lives and families or more towards educational goals that are religious, pragmatic, and material. The educational curriculum must be able to ensure the direction of students, not only make them current learners but they are preparing for the future. The concept of badawah and hadarah is a pillar of the situation. Students who are in cities and villages will certainly have different facilities and access to education, but the teaching provided has the same signs in order to create students as expected.